Comparative evaluation of femoral nerve block and intravenous fentanyl for positioning during spinal anaesthesia in surgery of femur fracture - Ashok Jadon; Sunil Kumar Kedia; Shreya Dixit; Swastika Chakraborty (Indian Journal of Anaesthesia, 2014)
Background: Spinal anaesthesia is the preferred technique to fix fracture of the femur. Extreme pain does not allow ideal positioning for this procedure. Intravenous fentanyl and femoral nerve block are commonly used techniques to reduce the pain during position for spinal anaesthesia however; results are conflicting regarding superiority of femoral nerve block over intravenous fentanyl. Aims: We conducted this study to compare the analgesic effect provided by femoral nerve block (FNB) and intra- venous (IV) fentanyl prior to positioning for central neuraxial block in patients undergoing surgery for femur fracture. Patients and Methods: In this randomized prospective study 60 patients scheduled for fracture femur operation under spinal were included. Patients were distributed in two groups through computer generated random numbers table; Femoral nerve block group (FNB) and Intravenous fentanyl group (FENT). In FNB group patients received FNB guided by a peripheral nerve stimulator (Stimuplex; B Braun, Melsungen, AG) 5 minutes prior to positioning. 20mL, 1.5% lidocaine with adrenaline (1:200,000) was injected incrementally after a negative aspiration test. Patients in the fentanyl group received injection fentanyl 1 μg/kg IV 5 mins prior to positioning. Spinal block was performed and pain scores before and during positioning were recorded. Statistical analysis was done with Sigmaplot version-10 computer software. Student t-test was applied to compare the means and P < 0.05 was taken as significant. Results: VAS during positioning in group FNB: 0.57 ± 0.31 versus FENT 2.53 ± 1.61 (P = 0.0020). Time to perform spinal anesthesia in group FNB: 15.33 ± 1.64 min versus FENT 19.56 ± 3.09 min (P = 0.000049). Quality of patient positioning for spinal anesthesia in group FNB 2.67± 0.606 versus FENT 1.967 ± 0.85 (P = 0.000027). Patient acceptance was less in group FENT (P = 0.000031). Conclusion: Femoral nerve block provides better analgesia, patient satisfaction and satisfactory positioning than IV fentanyl for position during spinal anaesthesia in patients of fracture femur.